Congenital Syphilis Case Surveillance in South Africa 2017–19: Experience, Challenges and Opportunities. (7th September 2021) - Morifi, Mabore; Malevu, Ntebogeleng; Odayan, Sharika; McCarthy, Kerrigan; Kufa, Tendesayi
Abstract: Background: Untreated or inadequately treated maternal syphilis infection may be transmitted from mother to child resulting in congenital syphilis (CS) infection. In South Africa (SA), CS is a notifiable medical condition (NMC). The NMC surveillance system (NMCSS) was improved by introducing an electronic notification application, a new case notification form and training resources in July 2017. We describe CS surveillance in SA and report on experiences from implementing an improved NMCSS from August 2017 to December 2019. Methods: We present the CS case definition, data collected by the CS case investigation and notification forms and data flow through the NMCSS. Descriptive statistics were used to analyse CS notifications received from August 2017 to December 2019. Qualitative inductive analysis of the stakeholder communications diary was conducted to identify CS surveillance challenges. Results: There were 418 CS notifications submitted from 80 facilities in 35 out of 52 districts. Of the notified cases, 194 (46.8%) were male and the median age at notification was 7 days (interquartile range: 3–16 days). The majority were diagnosed in hospital (98.6%). KwaZulu–Natal Province notified the most cases (52.9%) followed by Gauteng (28.0%). Challenges in CS surveillance included the lack of awareness of the CS case definition, completed paper-based notifications not reaching the NMCSS and the limited ability of the system to distinguish improved notifications from increase in disease burden. Conclusion: Improved CS surveillance through NMCSS was implemented in SA. Training, support and mentoring on CS and the notification system will be needed to inform elimination efforts.